THE SIGNIFICANCE OF INTEREST FOR ACTIVE LEGITIMATION IN ROMAN CIVIL PROCEDURE - Guzhva, Anton (Zeszyty Prawnicze, 2023)
The aim of this article is to examine the importance of interest for an applicant’s right to legal protection in Roman civil procedure. I establish a connection between the interest of the authorized person and his right to sue or apply for an interdict by reviewing the sources of Roman law concerning a claim for theft or on the grounds of a contract of mandate or actio ad exhibendum, as well as interdicts on the protection of posession. This enables me to define the persons with a right to enjoy these forms of procedural protection thanks to having a proven interest. Thus, the contractor who is robbed of the subject of his contract had the right to sue for theft, since he was responsible for the safekeeping of the thing. So, too, was the creditor of a pledge, since he had an interest in owning the subject of the pledge. The applicant for a right to actio ad exhibendum needed to have an interest in the presentation of the thing, regardless of whether he was its owner. The person entitled to bring an action on the grounds of a contract of mandate was the principal, if he had an interest in the execution of the commission. Interest was also the necessary condition for an applicant to claim a right to the quod vi aut clam interdict, which could be granted not only to the owner of the thing, but also to other persons whose interests were infringed.